DRD and GRIN2B polymorphisms and their association with the development of impulse control behaviour among Malaysian Parkinson’s disease patients - Zainal Abidin, S.; Tan, E.L.; Chan, S.C.; Jaafar, Ameerah; Lee, A.X.; Abd Hamid, M.H.N.; Abdul Murad, N.A.; Pakarul Razy, N.F.; Azmin, S.; Ahmad-Annuar, Azlina; Lim, Shen Yang; Cheah, P.S.; et al. (BioMed Central, 2015)
Background: Impulse control disorder (ICD) and behaviours (ICB) represent a group of behavioural disorders that have become increasingly recognised in Parkinson's disease (PD) patients who previously used dopaminergic medications, particularly dopamine agonists and levodopa. It has been suggested that these medications can lead to the development of ICB through the abnormal modulation of dopaminergic transmission and signalling in the mesocorticolimbic dopaminergic system. Several studies have reported an association between polymorphisms in the dopamine receptor (DRD) and N-methyl-D-aspartate 2B (GRIN2B) genes with the development of ICB in PD (PD-ICB) patients. Thus, this study aimed to investigate the association of selected polymorphisms within the DRD and GRIN2B genes with the development of ICB among PD patients using high resolution melt (HRM) analysis. Method: We used high resolution melt (HRM) analysis to genotype 11 polymorphisms in 5 DRD genes [DRD1 (rs4532, rs4867798 and rs265981), DRD2 (ANKK1 rs1800497, rs104894220 and rs144999500), DRD3 (rs3732783 and rs6280), DRD4 (rs1800443), and DRD5 (rs144132215)] and 1 polymorphism in GRIN2B (rs7301328) in PD patients with (cases, n = 52) and without (controls, n = 39) ICB. Cases were obtained from two tertiary movement disorder centres [UKMMC (n = 9) and UMMC (n = 43)]. At both centres, the diagnosis of ICB was made using the QUIP questionnaire. Controls were recruited from PD patients who attended UKMMC and were found to be negative for ICB using the QUIP questionnaire. Results: The HRM analysis showed that 7 of 11 polymorphisms [DRD1 (rs4532, rs4867798, and rs265981), DRD2 (ANKK1 rs1800497), DRD3 (rs3732783 and rs6280), and GRIN2B (rs7301328)] exhibited a clear distinction between wild-type and variant alleles. Variants of DRD2/ANKK1 rs1800497 (OR = 3.77; 95% CI, 1.38-10.30; p = 0.0044), DRD1 rs4867798 (OR = 24.53; 95% CI, 1.68-357.28; p = 0.0054), DRD1 rs4532 (OR = 21.33; 95% CI, 1.97-230.64; p = 0.0024), and GRIN2B rs7301328 (OR = 25.07; 95% CI, 1.30-483.41; p = 0.0097) were found to be associated with an increased risk of developing ICB among PD patients. Conclusion: Our findings suggest that polymorphisms in dopamine [DRD1 (rs4532 and rs4867798) and DRD2/ANKK1 rs1800497] and glutamate (GRIN2B rs7301328) receptor genes confer increased risk of ICB development among PD patients.